Supercapacitors Based on Nickel Oxide/Carbon Materials Composites. (26th October 2010) - Lota, Katarzyna; Sierczynska, Agnieszka; Lota, Grzegorz
Abstract : In the thesis, the properties of nickel oxide/active carbon composites as the electrode materials for supercapacitors are discussed. Composites with a different proportion of nickel oxide/carbon materials were prepared. A nickel oxide/carbon composite was prepared by chemically precipitating nickel hydroxide on an active carbon and heating the hydroxide at 300  ∘ C in the air. Phase compositions of the products were characterized using X-ray diffractometry (XRD). The morphology of the composites was observed by SEM. The electrochemical performances of composite electrodes used in electrochemical capacitors were studied in addition to the properties of electrode consisting of separate active carbon and nickel oxide only. The electrochemical measurements were carried out using cyclic voltammetry, galvanostatic charge/discharge, and impedance spectroscopy. The composites were tested in 6 M KOH aqueous electrolyte using two- and three-electrode Swagelok systems. The results showed that adding only a few percent of nickel oxide to active carbon provided the highest value of capacity. It is the confirmation of the fact that such an amount of nickel oxide is optimal to take advantage of both components of the composite, which additionally can be a good solution as a negative electrode in asymmetric configuration of electrode materials in an electrochemical capacitor.